Design and Build Low-Cost Power Hammer Machine Based on Throttle Stomp - Agus Sifa; Tito Endramawan; Dedi Suwandi; Ibnu Farhan; Rivay Febrio Maulana (Universitas Negeri Padang, 2022)
Metal forming uses plastic deformation to change the shape of the workpiece. Deformation or change in shape results from the use of a tool which is usually called a die. The die provides stresses that exceed the yield strength of the material (plastic). The forging process is one of several types of metal forming. A power hammer machine is a machine used for the formation of a product in the manufacturing process, namely with a system of continuous forging/pressure on the specimen so that the deformed specimen becomes denser and stronger according to the desired shape. The forging process is superior to other processes such as casting and machining. The effectiveness of the forging process is characterized by low costs, high productivity, and high product quality. The cold forging process needs to be improved to reduce the occurrence of fine cracks and defects. The main factor is the quality of forging results by planning the design and production of the right die, improving product quality, and reducing the number of defective products to encourage industrial competitiveness. The method in this research is the process of making the design and calculation of the main components and making the power hammer machine. The results of the design and manufacture of the power hammer machine obtained that the impact force from the design was 58.3 Kg, the rotation of the drive shaft to drive the hammer was 206.5 Rpm, the diameter of the driving shaft was 12.36 mm with the one made of 16 mm, the torque on the driving motor was 77.9 Nm, the minimum power designed is 2.2 hp with a rotation of 2800 Rpm, and is selected for the manufacture of 3 Hp, the electrical system is on / off using a throttle stomp.